Megathyrsus maximus breeding: General combining ability and heterosis of plant height using the North Carolina II Mating Design - Hernández, Luis Miguel; Jauregui, Rosa (CGIAR Initiative on Accelerated Breeding, 2023)
Combining ability and heterosis were studied in a 9 × 27 North Carolina II mating design to investigate the inheritance of agronomic traits of interest in Megathyrsus maximus (Jacq.) B.K. Simon & S.W.L. Jacobs. The main objective is to identify the best apomictic tester to be used as parent in recurrent selection breeding scheme (Hernández & Castiblanco, 2021).